Toroidal coupling in the kinetic response to edge magnetic perturbations. (26th October 2017) - Spizzo, G.; Agostini, M.; Scarin, P.; White, R.B.; Schmitz, O.; Spolaore, M.; Terranova, D.; Veranda, M.; Vianello, N.
Abstract: The magnetic topology of the stochastic edge of a helical reversed-field pinch, with helicity m / n, shows to be deeply influenced by higher harmonics ( m ± 1 ) / n, with the same n, due to toroidal coupling. As a consequence, by measuring kinetic quantities in a particular θ, ϕ location, one can incur in substantial errors or mis-interpretations of the kinetic plasma response: only a full 3D coverage of θ, ϕ angles can reveal the real topology of the plasma. This can be a caveat for MP application in tokamaks, because it shows that toroidal and poloidal sidebands, though smaller than the base mode by a factor ̃ ϵ = a / R, can have a sizable effect on the kinetic response of the edge plasma, and thus on related issues (for example, ELM stabilization and suppression).